A GIS-based interval type-2 fuzzy set for public bread factory site selection. Issue 6 (21st September 2018) - Deveci, Muhammet; Akyurt, Ibrahim Zeki; Yavuz, Selahattin
Abstract : Purpose: The purpose of this paper is to present a new public bread factory location selection for Istanbul Metropolitan Municipality (IMM). Design/methodology/approach: A two-stage methodology is proposed to determine the location for the public bread factory facility. This framework is based on both geographic information systems (GIS) and multi-criteria decision-making (MCDM) techniques. The first stage of the methodology aims to decrease the number of possible alternative locations to simplify the selection activity by applying GIS; the second stage utilises interval type-2 fuzzy MCDM approach to exactly determine the public bread factory site location. Findings: In this study, the authors present weighted normalised-based interval type-2 hesitant fuzzy and interval type-2 hesitant fuzzy sets (IT2HFSs)-based compressed proportional assessment (COPRAS) methods to overcome facility location selection problem for a fourth public bread factory in Istanbul. Practical implications: The results show that the proposed approach is practical and can be employed by the bakery industry. Originality/value: In this study, the authors present a two-stage methodology for public bread factory site selection. In the first stage, the number of alternatives is reduced by the GIS. In the second stage, an interval type-2 fuzzy set is implemented for the evaluation of public bakery factory site alternatives. A new integrated approach based on COPRAS method and weighted normalised with IT2HFSs is proposed.